2022
DOI: 10.1097/pg9.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Foreign Body Ingestions Amidst the Coronavirus 2019 Pandemic at a Tertiary Care Children’s Hospital

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Pediatric EFBs have become increasingly prevalent and pose a significant danger to children. 2,3,20,21 Although risk factors such as anatomical abnormalities and younger age have been associated with higher rates of EFB ingestion, 22,23 SES as a risk factor has never been studied. Determining the influence of socioeconomic factors on EFB ingestion is important to further understand health disparities in children and to help target primary prevention measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric EFBs have become increasingly prevalent and pose a significant danger to children. 2,3,20,21 Although risk factors such as anatomical abnormalities and younger age have been associated with higher rates of EFB ingestion, 22,23 SES as a risk factor has never been studied. Determining the influence of socioeconomic factors on EFB ingestion is important to further understand health disparities in children and to help target primary prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric EFBs have become increasingly prevalent and pose a significant danger to children 2,3,20,21 . Although risk factors such as anatomical abnormalities and younger age have been associated with higher rates of EFB ingestion, 22,23 SES as a risk factor has never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This was further suggested in other studies documenting significant increases in foreign-body ingestions, which mentioned that most ingestions in children occur in the home environment and increased time spent at home by children was seen during the pandemic. 30 , 31 Although some included studies reported foreign bodies by anatomical location, there was not enough data reported to analyze presentation rates by location.…”
Section: Discussionmentioning
confidence: 99%
“…Current pandemic crisis contributed several obvious reasons to shoot-up FBI cases. 18 As reported a remarkable higher rate of potentially fatal FBIs patients have been admitted to pediatric emergency departments during COVID-19 pandemic especially second pandemic period (2020-21) in different countries across the world. 19,20…”
Section: Epidemiologymentioning
confidence: 97%